Clinical evaluation of an endorectal immobilization system for use in prostate hypofractionated Stereotactic Ablative Body Radiotherapy (SABR) - Nicolae, Alexandru (Radiat Oncol, 2015)
BACKGROUND: The objective of this study was to evaluate a novel prostate endorectal immobilization system (EIS) for improving the delivery of hypofractionated Stereotactic Ablative Body Radiotherapy (SABR) for prostate cancer. METHODS: Twenty patients (n = 20) with low- or intermediate-risk prostate cancer (T1-T2b, Gleason Score < 7, PSA ≤ 20 ng/mL), were treated with an EIS in place using Volumetric Modulated Arc Therapy (VMAT), to a prescription dose of 26 Gy delivered in 2 fractions once per week; the intent of the institutional clinical trial was an attempt to replicate brachytherapy-like dosimetry using SABR. EBT3 radiochromic film embedded within the EIS was used as a quality assurance measure of the delivered dose; additionally, prostate intrafraction motion captured using pre- and post-treatment conebeam computed tomography (CBCT) scans was evaluated. Treatment plans were generated for patients with- and without the EIS to evaluate its effects on target and rectal dosimetry. RESULTS: None of the observed 3-dimensional prostate displacements were ≥ 3 mm over the elapsed treatment time. A Gamma passing rate of 95.64 ± 4.28 % was observed between planned and delivered dose profiles on EBT3 film analysis in the low-dose region. No statistically significant differences between treatment plans with- and without-EIS were observed for rectal, bladder, clinical target volume (CTV), and PTV contours (p = 0.477, 0.484, 0.487, and 0.487, respectively). A mean rectal V80% of 1.07 cc was achieved for plans using the EIS. CONCLUSIONS: The EIS enables the safe delivery of brachytherapy-like SABR plans to the prostate while having minimal impact on treatment planning and rectal dosimetry. Consistent and reproducible immobilization of the prostate is possible throughout the duration of these treatments using such a device.